2012
DOI: 10.1111/j.1468-3083.2012.04516.x
|View full text |Cite
|
Sign up to set email alerts
|

Acne sans P. acnes

Abstract: Acne vulgaris is a common disease that carries an enormous financial and psychosocial impact. Androgens, excessive sebum production, ductal hypercornification, changes in the microbial flora, as well as inflammation and immunological host reactions are considered the major contributors to acne pathogenesis. Despite extensive research on acne pathogenesis, the exact sequence of events and their possible mechanisms leading to the development of a microcomedone and its transformation into an inflamed lesion has r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 105 publications
0
27
1
5
Order By: Relevance
“…Initiation of acne likely does not require P. acnes , as shown by the fact that propionibacteria are not always isolated from acne lesions [ 17 ] . However, propionibacteria contribute to disease aggravation by secreting infl ammation-promoting metabolites such as lipases, which release (irritant) free fatty acids from triglycerides, as well as proteases, hyaluronidases, and chemotactic factors.…”
Section: Pathogenesismentioning
confidence: 99%
“…Initiation of acne likely does not require P. acnes , as shown by the fact that propionibacteria are not always isolated from acne lesions [ 17 ] . However, propionibacteria contribute to disease aggravation by secreting infl ammation-promoting metabolites such as lipases, which release (irritant) free fatty acids from triglycerides, as well as proteases, hyaluronidases, and chemotactic factors.…”
Section: Pathogenesismentioning
confidence: 99%
“…Buffers used were the following: buffer A, 25 mM Tris-HCl (pH 7.1), 5% glycerol, 700 mM NaCl, 6 mM ␤-mercaptoethanol, 0.1 mM phenylmethylsulfonyl fluoride (PMSF), 0.1 mM benzamidine; buffer B, 25 mM Tris-HCl (pH 7.1), 300 mM NaCl, 5% glycerol, 20 mM imidazole, 6 mM ␤-mercaptoethanol, 0.1 mM PMSF, and 0.1 mM benzamidine; buffer C, 25 mM Tris-HCl (pH 7.1), 300 mM NaCl, 5% glycerol, 300 mM imidazole, 6 mM ␤-mercaptoethanol, 0.1 mM PMSF, 0.1 mM benzamidine; buffer D, 20 mM Tris-HCl (pH 7.1), 100 mM NH 4 Cl, 5% glycerol, 6 mM ␤-mercaptoethanol, 0.1 mM EDTA; buffer E, 10 mM Tris-HCl (pH 7.7), 10 mM magnesium acetate, 60 mM NH 4 Cl.…”
Section: Methodsmentioning
confidence: 99%
“…The organism catabolizes sebaceous triglycerides, using the glycerol moiety as a carbon source without catabolizing the fatty acids. While this species has been advocated to play a fundamental role in the etiogenesis of acne (5,6), a significant controversy remains as to how important a role P. acnes plays (4,7). Recent metagenomic studies have confirmed it to be the major inhabitant of pilosebaceous units (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are various forms of acne, and so different sequences of events are likely. A severe form of acne, known as ‘chloracne' and leading to the formation of metabolising acquired dioxin-induced skin hamartoma (MADISH) [3,4], is clearly associated with the exposure of chemicals such as polychlorinated dibenzodioxins and dibenzofurans [5,6,7], and does not require the presence of Propionibacterium acnes [8]. The main feature of these chemicals is the activation of aromatic hydrocarbon receptor (AhR).…”
mentioning
confidence: 99%